Advanced DPA Theory and Practice Towards the Security Limits of Secure Embedded Circuits - Peeters, Eric.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Advanced DPA Theory and Practice provides a thorough survey of new physical leakages of embedded systems, namely the power and the electromagnetic emanations. The book presents a thorough analysis about leakage origin of embedded system. This book examines the systematic approach of the different aspects and advanced details about experimental setup for electromagnetic attack. The author discusses advanced statistical methods to successfully attack embedded devices such as high-order attack, template attack in principal subspaces, machine learning methods. The book includes theoretical framework to define side-channel based on two metrics: mutual information and success rate.
General Introduction -- Side-Channel Cryptanalysis: a brief survey -- CMOS devices: sources and models of emanation -- Measurement of the power consumption -- Electromagnetic Leakage -- Statistical Tools -- Higher Order Attacks -- Towards the Evaluation of an Implementation against Side-Channel Attacks -- General Conclusion and Possible Further Directions.
Keywords: Engineering; Data protection; Data structures (Computer science).; Electronics; Systems engineering; Engineering; Electronics and Microelectronics, Instrumentation; Systems and Data Security; Circuits and Systems; Data Structures, Cryptology and Information Theory